2015
DOI: 10.1111/eth.12413
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Parental Care and Food Deprivation on Regulation of Body Mass in a Burying Beetle

Abstract: Changes in adult body mass during breeding can reveal how parents prepare energetically for care, the stress of care, and the need to terminate care in a state conducive for future reproduction. Interpreting changes in parent mass can be difficult, however, because temporal variation in body mass may reflect a constraint imposed by the stress of care, revealing conflict within the family, or a shift to a new body mass optimum adaptive for a different stage of the breeding cycle. Here, we examined the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Meanwhile, resource acquisition prior to breeding influenced mass gain over the reproductive attempt with starved females gaining more mass than nonstarved females. This result likely reflects that resource acquisition prior to breeding determines female nutritional condition and starved females may feed more from the carcass than nonstarved females to replenish their energy stores (Gray et al., ; Keppner, Ayasse, & Steiger, ; Trumbo & Xhihani, ). In addition, starved females had fewer offspring alive at eclosion but only when breeding on a large carcass (see below for discussion of this interaction).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, resource acquisition prior to breeding influenced mass gain over the reproductive attempt with starved females gaining more mass than nonstarved females. This result likely reflects that resource acquisition prior to breeding determines female nutritional condition and starved females may feed more from the carcass than nonstarved females to replenish their energy stores (Gray et al., ; Keppner, Ayasse, & Steiger, ; Trumbo & Xhihani, ). In addition, starved females had fewer offspring alive at eclosion but only when breeding on a large carcass (see below for discussion of this interaction).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we made the exploitation of the carcass more essential for one or both caring parents by manipulating their nutritional condition before breeding. In fact, a study of Trumbo & Xhihani () demonstrated that food‐deprived females increase their carrion consumption in Nicrophorus orbicollis . Poor condition of the female because of a prereproductive lack of food is also known to lead to a reduced clutch size and offspring number (Steiger et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Burying beetles reach their heaviest mass at the start of post‐natal parental care, approximately 10% greater than the mass maintained in beetles searching for a carcass that have access to food (Trumbo & Rauter, ). Burying beetles reach this elevated target mass during care despite wide differences in body size and starvation periods prior to carcass discovery, further suggesting adaptive mechanisms of sensing and regulating body mass (Trumbo & Xhihani, ).…”
Section: Discussionmentioning
confidence: 97%
“…The high nutritional value of a complete food source such as carrion allows rapid mass gain (including recovery from starvation), a response that is crucial to understanding many aspects of life history that otherwise appear risky or wasteful. By exploring how rapidly these engorging feeders can recover body mass, the present study provides a nutritional framework for understanding (i) why larvae of small mass can emerge as an adult with a limited energy reserve and only days from starvation; (ii) why food‐deprived females experience only a slight delay in utilizing a discovered carcass for breeding (Steiger, ); (iii) why females can afford to produce a large excess of eggs on a small carcass even though many of these young will be later cannibalized (Bartlett, ); (iv) why subordinate females produce a large number of eggs that have a low probability of being cared for by a dominant adult, even if they have little access to the carcass (Müller et al ., ; Eggert et al ., ); and (v) why care‐givers can afford considerable weight loss during the active stage of parental care (Trumbo & Rauter, , Trumbo & Xhihani, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation